Transfer Pricing in the Perspective of Foreign Ownership and Audit Quality: A Study of Company Size Moderation - Kodriyah, Kodriyah; Mahardini, Nikke Yusnita; Burhanudin, Burhanudin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to examine the influence of foreign ownership and audit quality on transfer pricing, as well as the role of company size as a moderation variable, in manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange. The research method is quantitative and causal, and data are collected from annual financial statements for the 2020–2024 period. The analysis techniques used are multiple linear regression and Moderated Regression Analysis (MRA). The results show that foreign ownership and audit quality significantly affect transfer pricing. The moderation test showed that firm size significantly moderated the relationship between foreign ownership and audit quality in transfer pricing. This means that the influence of these two variables tends to be stronger in large-scale companies. These findings confirm the importance of oversight of ownership structures and audit quality, especially in large companies that have complex cross-border transactions.